2018
DOI: 10.1016/j.foreco.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Are litterfall and litter decomposition processes indicators of forest regeneration in the neotropics? Insights from a case study in the Brazilian Amazon

Abstract: Litterfall plays an important role in nutrient cycling and maintenance of soil fertility in terrestrial ecosystems. We gauged the effects of anthropogenic impacts on the production, decomposition and seasonality of litterfall in primary and secondary forests within a tropical landscape of the Brazilian Amazon. We hypothesized that leaf litter quantity and quality would differ in line with forest disturbance and that these changes would translate into dissimilar decomposition rates. If proved, these processes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 79 publications
1
18
0
12
Order By: Relevance
“…Litterfall and litter decomposition are key ecosystem functions that release nutrients to forest soils and contribute a significant fraction of carbon (C) emissions into the atmosphere (Vitousek & Sanford, ; Berg & McClaugherty, ). Comparing the rate of these processes in successional forests to those in primary forests can be a useful indicator of recovery (Powers & Marín‐Spiotta, ; da Silva, Périco, Dalzochio, Santos, & Cajaiba, ) and informs modeling of global environmental change. Studies examining relationships between biodiversity and ecosystem functions in tropical secondary settings have shown that species richness of some taxonomic groups (mainly plants) and some ecosystem functions (biomass and productivity) are positively correlated (Lohbeck et al, ; Bu, Zang, & Ding, ; Lasky et al, ; Arroyo‐Rodriguez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Litterfall and litter decomposition are key ecosystem functions that release nutrients to forest soils and contribute a significant fraction of carbon (C) emissions into the atmosphere (Vitousek & Sanford, ; Berg & McClaugherty, ). Comparing the rate of these processes in successional forests to those in primary forests can be a useful indicator of recovery (Powers & Marín‐Spiotta, ; da Silva, Périco, Dalzochio, Santos, & Cajaiba, ) and informs modeling of global environmental change. Studies examining relationships between biodiversity and ecosystem functions in tropical secondary settings have shown that species richness of some taxonomic groups (mainly plants) and some ecosystem functions (biomass and productivity) are positively correlated (Lohbeck et al, ; Bu, Zang, & Ding, ; Lasky et al, ; Arroyo‐Rodriguez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The study was developed in the municipality of Uruará, southwestern Pará state, northern Brazil (−03°43′27″S; −53°44′8″W, Figure S1). The region is located approximately at 1000 km from Belém, the capital of Pará state, and is crossed by the Transamazon Highway (official designation BR‐230) (da Silva, Périco, Dalzochio, Santos, & Cajaiba, ). Forest is the dominant land use/land cover (LULC) while deforestation is concentrated mainly in the south‐central part of the territory and near the main roads.…”
Section: Methodsmentioning
confidence: 99%
“…For these reasons, the litter is essential to the Amazonian region for delivering nutrients and sustaining the forest. 70 Because of the temperature, rainfall, and microbiological diversity, the OM of the top layer is easily degraded. Therefore, the OM stability from ADE may be useful for reproducing a model of anthropogenic OM to create new anthropic soils that improve the soil properties and OM quality.…”
Section: Features Of Soil Organic Matter Compositionmentioning
confidence: 99%